2023
DOI: 10.3390/v15020483
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Winged Teals in Guatemala and Their Potential Role in the Ecology of H14 Subtype Influenza a Viruses

Abstract: Wild aquatic birds are considered the natural hosts of 16 HA (H1–H16) and 9 NA (N1–N9) subtypes of influenza A viruses (FLUAV) found in different combinations. H14 FLUAVs are rarely detected in nature. Since 2011, H14 FLUAVs have been consistently detected in Guatemala, leading to the largest collection of this subtype from a single country. All H14 FLUAVs in Guatemala were detected from blue-winged teal samples. In this report, 17 new full-length H14 FLUAV genome sequences detected from 2014 until 2019 were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In Eurasia, five H14 viruses were sequenced from samples collected in 1982, and more contemporary strains include one collected in 2006, six between 2014 and 2019 from Eastern Europe/Western Asia, and a single sequence from Egypt from 2017. In contrast, all North American samples were collected between 2010 and 2019, and appear to originally derive from the Eurasian lineage [ 38 ], likely through a single introduction, sharing a common ancestor with A/garganey/Ukraine/2006 with a mean time of most recent common ancestor (tMRCA) of April 2004 (October 2002–August 2005, 95% highest posterior density (HPD)) and have been maintained in local bird populations.
Figure 2.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eurasia, five H14 viruses were sequenced from samples collected in 1982, and more contemporary strains include one collected in 2006, six between 2014 and 2019 from Eastern Europe/Western Asia, and a single sequence from Egypt from 2017. In contrast, all North American samples were collected between 2010 and 2019, and appear to originally derive from the Eurasian lineage [ 38 ], likely through a single introduction, sharing a common ancestor with A/garganey/Ukraine/2006 with a mean time of most recent common ancestor (tMRCA) of April 2004 (October 2002–August 2005, 95% highest posterior density (HPD)) and have been maintained in local bird populations.
Figure 2.
…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the first H14 sequences from Guatemala, the first Cambodian H14 contained the PDKQTK↓GLF cleavage site motif, which is quite unusual amongst IAVs. Cambodian H14 viruses sequenced one month later, at the same duck farm, however contained the PDKQTR↓GLF cleavage site motif, a more “classic” motif [ 38 ]. Currently, it is unknown how these differences in cleavage site motifs of H14 viruses affect HA functioning in terms of replication, virulence, and transmission in wild birds and their spillover hosts such as poultry and potentially mammalian species [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their scavenging habits and migratory behavior in the Americas, turkey vultures ( Cathartes aura ) could also contribute to the spread of H5N1 ( 37 ). Conversely, Anseriformes were involved in few outbreaks in Chile, despite being recognized as key hosts in the epidemiology of avian influenza viruses, both as reservoirs ( 40 , 45 , 50–52 ) or as long-distance spreaders ( 53 ). As previously shown for a wide variety of low pathogenic avian influenza viruses in Chile ( 52 , 54 ), it is possible that as H5N1 becomes ezootic, and with Anseriformes start playing more relevant epidemiological roles, such as acting as virus reservoirs ( 6 , 44 ) or even suffering the consequences of disease ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…This wave like spreading is likely associated to the movement of wild birds, although no information is currently available on the hosts species disseminating the virus across space in South America. Although pelicans, boobies, gulls and cormorants have been the most affected species in Chile and Peru (Gamarra-Toledo et al 2023a), and ducks and teals are recognized as reservoirs and spreaders of avian influenza in other regions (Siembieda et al 2010, Torrontegi et al 2019, Ortiz et al 2023, it is unknown which species are responsible for the observed pattern of spread in Chile, given their movement behavior with most of these species lacking large-scale migrations (Gonzalez-Reiche and Perez 2012, Afanador-Villamizar et al 2017). Thus, further research combining spatial ecology and genetic analyses could help solving this relevant question.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Anseriformes were involved in few outbreaks in Chile (Fig. 1), despite being recognized as key hosts in the epidemiology of avian influenza viruses, both as reservoirs (Gaidet et al 2012, Verhagen et al 2014, Jiménez-Bluhm et al 2018, Torrontegi et al 2019, Ortiz et al 2023 or as long-distance spreaders (Keawcharoen et al 2008). As previously shown for a wide variety of low pathogenic avian influenza viruses in Chile (Jiménez-Bluhm et al 2018, Ruiz et al 2021, it is possible that as H5N1 becomes enzootic in Chile, Anseriformes start playing more relevant epidemiological roles, such as acting as virus reservoirs (Torrontegi et al 2019 or even suffering the consequences of disease (Keawcharoen et al 2008).…”
Section: Discussionmentioning
confidence: 99%